Clinical application of repetitive transcranial magnetic stimulation in the treatment of chronic pelvic pain syndrome: a scoping review - Luo, Chunmei; Zhang, Baocheng; Zhou, Jing; Yu, Keqiang; Chang, Degui (Frontiers in Neurology, 2025)
IntroductionChronic pelvic pain syndrome is a common condition characterized by persistent symptoms that are difficult to treat. Repetitive transcranial magnetic stimulation (rTMS) is considered a safe treatment option for alleviating chronic pelvic pain, but different stimulation protocols can affect pain relief outcomes. Establishing an optimal stimulation protocol can enhance the uniformity and consistency of rTMS to provide a potentially effective therapeutic intervention. This review sought to systematically review and assess the existing literature on transcranial magnetic stimulation in patients experiencing chronic pelvic pain syndrome, evaluate the therapeutic efficacy, and determine the most effective stimulation protocol.MethodsA comprehensive search was conducted across three databases, supplemented by manual searches. Two researchers independently reviewed and extracted relevant studies and subsequently performed a thorough analysis of all available clinical data.ResultsA total of eight studies were ultimately incorporated into the analysis. These comprised two randomized controlled trials, one self-controlled trial, two case reports, and three prospective studies. All studies demonstrated a notable reduction in pain scores post-treatment.ConclusionrTMS has demonstrated efficacy in alleviating pain in individuals suffering from chronic pelvic pain syndrome. It is regarded as a safe intervention with minimal adverse effects. Nonetheless, the variability observed across studies hindered our ability to conclusively determine the most effective stimulation sites and parameters. Additional research is essential to reduce bias, enhance methodological rigor, and ascertain the optimal conditions and indications for brain stimulation to optimize the therapeutic effectiveness of rTMS.Systematic Review Registrationhttps://inplasy.com/projects/, identifier INPLASY2023120112.